1993
DOI: 10.1111/j.1745-9125.1993.tb01136.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Imprisonment Decisions

Abstract: Guidelines sentencing data from Pennsylvania for the years 1985–1987 are analyzed to assess the influence of gender on judges' imprisonment decisions. These data provide detailed information on offense severity and prior record, permit statistical controls for other variables thought to affect imprisonment decisions, cover a fairly comprehensive list of common‐law offenses (with adequate sample size), and contain judges' dispositional‐departure reasons for sentences outside the guidelines schema. The data—anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
495
6
13

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 426 publications
(546 citation statements)
references
References 28 publications
32
495
6
13
Order By: Relevance
“…Empirical research has confirmed that these social characteristics do indeed affect evaluations of offender dangerousness and offense severity (Albonetti 1991(Albonetti , 1997Bridges and Crutchfield 1988;Bridges and Steen 1998;Fearn 2005;Kautt 2009b;Kramer and Steffensmeier 1993;Moore and Miethe 1986;Steffensmeier and Demuth 2000;Steffensmeier, Ulmer and Kramer 1998;Zatz 1984). But social structure, particularly in small groups, is not determined solely by an individual's own characteristics but rather those characteristics relative to the characteristics of others (Berger and Webster 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical research has confirmed that these social characteristics do indeed affect evaluations of offender dangerousness and offense severity (Albonetti 1991(Albonetti , 1997Bridges and Crutchfield 1988;Bridges and Steen 1998;Fearn 2005;Kautt 2009b;Kramer and Steffensmeier 1993;Moore and Miethe 1986;Steffensmeier and Demuth 2000;Steffensmeier, Ulmer and Kramer 1998;Zatz 1984). But social structure, particularly in small groups, is not determined solely by an individual's own characteristics but rather those characteristics relative to the characteristics of others (Berger and Webster 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude by discussing our findings in the larger context of applying sociological accounts of status and emotion to the sentencing literature and show how these literatures are jointly instructive in improving our understanding of the mechanisms that affect the criminal adjudication process. Steffensmeier et al (1998) argue that judges consider three focal concerns when making sentencing decisions: blameworthiness, community protection, and practical constraints (see also Spohn and Holleran 2000;Steffensmeier 1980;Steffensmeier and Demuth 2001;Steffensmeier et al 1993;Ulmer 1997;Ulmer and Johnson 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autrement dit, les juges seraient plus sévères envers les jeunes hommes noirs parce que 1) ils croient que leurs délits sont plus graves et requièrent une plus grande sévérité, 2) ils croient que leurs chances de récidiver sont plus grandes et agissent donc afi n de protéger la communauté et 3) ils croient qu'ils sont mieux préparés pour confronter une sentence sévère. Ces observations sont appuyées par des données qualitatives que les auteurs ont recueillies dans le cadre d'un projet complémentaire (Steffensmeier et al, 1993).…”
Section: Des Effets Isolés Ou L'intersection De Deux Identités ?unclassified
“…A number of studies have suggested that extra-legal variables are not independent (Doerner and Demuth, 2010;Steffensmeier et al, 1993, Steffensmeier et al, 1998. That is, it is not enough to simply look at race/ethnicity, gender, and age in isolation.…”
mentioning
confidence: 99%